KEDUDUKAN KONTAINER HOUSE SEBAGAI BENDA DAN WEWENANG NOTARIS DALAM PEMBUATAN AKTA PERALIHANNYA - Nindito, Ardani Retno (Magister Kenotariatan Universitas Surabaya, 2019)
The main subject of research is Container Position and Notary Authority in Making the Transitional Deed, with the formulation of the problem What is the position of Container House as a moving object and What is the notary's authority in making the Container House transitional deed. The conclusion is as follows: The position of Container House as a moving object, that container as an object that is valuable goods, property as a wealth, to the holder as the subject of rights is a private body or persoon, the right object is called an object, which means that the object of rights is object. Containers can be privately owned in the sense of individuals or legal entities, who are both legal subjects and can act according to law. Containers either as movable objects or immovable objects (planted in land parcels) can be used as objects of property rights in accordance with the provisions of Article 489 of the Civil Code. The authority of the notary in making Container House transfer deed, that the container building, the transfer of rights if built together with the land and the owner of the container building will divert the container along with the land can be proven by PPJB deed made before a notary or AJB made before PPAT. If the container building is only affixed, so that if it is transferred it does not damage the basic objects, the transfer of rights can be done with PPJB or with AJB made before a notary